News on the front: experiences with digital humanities in a History course in the suburbs of the great São Paulo area - Ferla, Luis Antonio Coelho (2020)
Drawing on the vagueness of what digital humanities are, and the view that sharing concrete experiences enriches that debate, the article offers an account of initiatives undertaken within the History Department of the Federal University of São Paulo (Unifesp). To give greater diversity to the material presented, projects were chosen from a research group and an undergraduate course. With centers of gravity in research and teaching, the projects analyzed propose greater recognition of the student’s role in digital humanities. The analysis also reinforces the paradox that digital humanities projects are institutionally undervalued, while facilitating the collaboration and the free circulation of knowledge.